2018
DOI: 10.3390/su10061849
|View full text |Cite
|
Sign up to set email alerts
|

Environmental Comfort Indicators for School Buildings in Sustainability Assessment Tools

Abstract: Decades ago, the only requirement to construct a building was to give men the right conditions for the execution of their work or leisure activities. With the development of knowledge about the internal and external environments of buildings, other requirements have been added such as the issue of user comfort. New construction techniques have been incorporated and new products have been created to improve internal environment comfort. This research addressed the importance of using indicators related to envir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
34
0
6

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 36 publications
(41 citation statements)
references
References 12 publications
1
34
0
6
Order By: Relevance
“…Therefore, anthropometric data would be necessary when designing any kind of furniture equipment [47]; considering ergonomic furniture may reduce these symptoms [48]. Ergonomics issues are a must in sustainability assessment tools [49].ICT facilities have become part of the physical learning environment, since elements such as computers or plugs are part of the design and operation of the classroom. In fact, their inclusion alters the classroom temperature and may require the use of artificial light instead of daylight, due to its reflection on the screens.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, anthropometric data would be necessary when designing any kind of furniture equipment [47]; considering ergonomic furniture may reduce these symptoms [48]. Ergonomics issues are a must in sustainability assessment tools [49].ICT facilities have become part of the physical learning environment, since elements such as computers or plugs are part of the design and operation of the classroom. In fact, their inclusion alters the classroom temperature and may require the use of artificial light instead of daylight, due to its reflection on the screens.…”
mentioning
confidence: 99%
“…Therefore, anthropometric data would be necessary when designing any kind of furniture equipment [47]; considering ergonomic furniture may reduce these symptoms [48]. Ergonomics issues are a must in sustainability assessment tools [49].…”
mentioning
confidence: 99%
“…In 1959, a renovation took place, with the creation of its main building, and from 2011 to 2013, EPE made a major renovation in this school. FHHS is an example of high school building standard in Portugal [22]. The high school students age varies between 15 and 18 years old (10th to 12th grade), corresponding to the third cycle of basic education.…”
Section: Methodsmentioning
confidence: 99%
“…A questionnaire was applied to students in the Francisco de Holanda high school about the level of discomfort related to ergonomic comfort, specifically about the proper sizing of the chair and table. The result of these questionnaires is reported in [22]. The result of this indicator is based on the result of this research, shown below.…”
Section: I18 Ergonomic Comfortmentioning
confidence: 99%
“…This work aims to improve methodologies related to high school performance by adding an indicator of sustainability awareness in assessment tools. The importance of fostering social awareness of the impacts of sustainability is undeniable [3]. This indicator allows for the use of schools as vehicles to disseminate the importance that the experience of sustainability has on people's lives, using students as tools since they can spread this idea in their families and in society, transforming it as part of their daily lives in a natural way.…”
Section: Introductionmentioning
confidence: 99%